Logistics Activity Affecting the Efficiency of Freight Transport Service Providers in Thanyaburi District, Pathum Thani Province - เขียวแก้ว, กมลชนก; เสมอวงษ์, ศรีสุภัค (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to (1) study the influence of personal factors on the efficiency of freight service providers in Thanyaburi District, Pathum Thani Province, (2) study the influence of logistics activities on the efficiency of freight service providers, and (3) compare the differences in logistics activities factors affecting the efficiency of freight service providers in Thanyaburi District, Pathum Thani Province. A questionnaire was used as the research instrument. The sample consisted of 385 freight service users, selected using Cochran’s formula and simple random sampling.The results revealed that most respondents were female, aged between 21–35 years, held a bachelor's degree, had 1–5 years of work experience, and earned an income between 10,001–20,000 baht. Opinions on logistics activities were rated at a high level, with transportation receiving the highest mean score. Opinions on the efficiency of freight service providers in all aspects were also rated at a relatively high level, with time efficiency receiving the highest mean score.Comparative analysis showed that logistics activities related to customer service significantly affected cost efficiency of freight service providers at the 0.05 significance level. However, differences in personal factors among respondents did not result in significant differences in overall efficiency.